2008
DOI: 10.1097/cmr.0b013e32830e391d
|View full text |Cite
|
Sign up to set email alerts
|

Cancer/testis genes expression in human melanoma cell lines

Abstract: We analyzed the expression of 15 cancer/testis and four melanoma differentiation antigens in 21 metastatic melanoma cell lines using reverse transcriptase-polymerase chain reaction (RT-PCR) assay. On the basis of morphological characteristics, tumor cell lines were divided into three groups with high, moderate, and low grade of differentiation. Evaluation of gene expression and melanoma cell morphology has revealed a correlation between increased expression of cancer/testis genes and differentiation grade of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 22 publications
1
14
0
4
Order By: Relevance
“…This study found the CTA prognostic value comparable to the current clinic-pathologic classifications [21]. A study by Mikhaylova et al revealed a correlation between the level of expression of CTAs and the differentiation of tumors with the more poorly differentiated cells exhibiting higher CTA levels [22]. …”
Section: Role In Prognosissupporting
confidence: 61%
“…This study found the CTA prognostic value comparable to the current clinic-pathologic classifications [21]. A study by Mikhaylova et al revealed a correlation between the level of expression of CTAs and the differentiation of tumors with the more poorly differentiated cells exhibiting higher CTA levels [22]. …”
Section: Role In Prognosissupporting
confidence: 61%
“…These findings are confirmed by the percentage of positive cases for CMCs, ranging from 6 to 93 % of the reports [9, 10, 14, 19, 34, 53]. Multiple markers RT-PCR assay has been established as the most reliable and sensitive approach to identify CMCs in peripheral blood or in draining lymph nodes of melanoma patients [9, 10, 21, 22, 36, 39, 43, 44, 61], becoming a valuable potential technique for monitoring the disease status [16, 47, 54, 59]. We could document the high sensitivity of RT-PCR assay able to evidence MCAM/MUC18 up to a single CMC, in dilution experiments.…”
Section: Discussionmentioning
confidence: 83%
“…All cells in culture carried the melanoma‐associated cell surface antigens Melan A, S100, Tyrosinase, and HMW [22]. Cytomorphology, karyologic data, and the cancer and testis genes expression profiles of these cell lines have been presented previously [21]. In the current study, we used three of the described melanoma cell lines, which were characterized by aggressive phenotype and high invasive potential (Mel Kor, Mel Cher, and Mel P ‐ Mel Kor, Mel Cher and Mel P melanoma cell lines were derived from surgical species of patients with disseminated melanoma), which have also been further characterized [41].…”
Section: Resultsmentioning
confidence: 99%